The relationships between race, employment, and self-rated health among older South Africans: exploring the mediating role of generalized anxiety - Yunus, Adams; Zhou, Lulin; Jamatutu, Seidu Abdulai; Tackie, Evelyn Agba (Frontiers in Public Health, 2024)
ObjectiveThis study explores the impact of race and employment status on self-rated health among older adults in South Africa. It reveals new insights by examining the mediating role of generalized anxiety. The findings highlight the importance of addressing these factors to improve the wellbeing of older adults.MethodsDrawing from Wave 5 of the National Income Dynamics Study—Coronavirus Rapid Mobile Survey, a cross-sectional survey encompassing a nationally representative cohort of South African adults, this research employs a sophisticated blend of logistic regression and structural equation modeling techniques.ResultsThe study reveals that race is strongly linked to self-rated health. Individuals of Colored and White backgrounds have lower odds of favorable self-rated health. Retirement has a positive impact on self-rated health. Generalized anxiety mediates the complex relationship between race and self-rated health.ConclusionsAddressing the imperative need to mitigate racial disparities in self-rated health and advance equitable healthcare access for older adults, targeted interventions are undeniably warranted.